The Effects of Non-Communicable Diseases and their Risk Factors on Malaysia’s Healthcare Expenditures - Fatin Nadia Zulfakairuddin; Sharifah Fairuz Syed Mohamad; Mazlynda Md Yusuf; Nurul Sima Mohamad Shariff; Sulieman Yhia (Semarak Ilmu Publishing, 2026)
Non-Indexed Publication